A high pressure shock tube study of 1-butene oxidation and its comparison with n-butane and alkenes. (1st October 2015) - Pan, Lun; Hu, Erjiang; Zhang, Jiaxiang; Tian, Zemin; Li, Xiaotian; Huang, Zuohua
Highlights: Ignition delay times of 1-butene were measured in a shock tube at wide experimental ranges. NUIG Aramco Mech 1.3, USC Mech 2.0 and LLNL C4 Mech were validated. Ignition delay times of 1-butene, n -butane, propene and ethylene were compared. NUIG Aramco Mech 1.3 was modified by sensitivity analysis. Abstract: Ignition delay times of 1-butene were measured behind reflected shock wave at the pressures of 1.2, 4.0, 16.0 atm, in temperature range of 1000–1700 K and equivalence ratios of 0.5, 1.0 and 2.0. Results show that ignition delay times exhibit the typical Arrhenius dependence on temperature, pressure, equivalence ratio and fuel concentration. A correlation was deduced from the experimental data. Comparison was made between the correlation and the previous data, and good agreement was achieved. Three widely used models, NUIG Aramco Mech 1.3 (Metcalfe et al., 2013), USC Mech 2.0 (Wang et al.) and LLNL C4 (Marinov et al., 1998) model, were used to predict the ignition delay times and comparison was made with the experimental data. None of these models can well reproduce the experimental data of 1-butene especially at lower temperature. Besides, comparative studies and qualitative analysis between C4 hydrocarbons and 1-alkenes with respect to the effect of CC bond and the carbon chain length were made at same argon–oxygen dilution ratios ( D ). Sensitivity analysis was made to identify the key reactions that control the ignition of 1-butene, and modifications for improving the model performance were recommended.